Herbal Remedy: An Alternate Therapy of Nonsteroidal Anti-Inflammatory Drug Induced Gastric Ulcer Healing. (6th May 2014) - Chatterjee, Ananya; Bandyopadhyay, Sandip K.
Abstract : Nonsteroidal anti-inflammatory drugs (NSAIDs) are one of the most commonly used therapeutic drug groups used worldwide for curing an array of health problems like pain, inflammation, cardiovascular complications, and many other diseases, but they may cause different side effects including gastroduodenal disorders. So, there is a growing interest and need to search for nontoxic, antiulcer formulations from medicinal plants to treat NSAIDs induced gastric ulcer. Extensive research has reported on many natural plants like Camellia sinensis, Phyllanthus emblica, Myristica malabarica, Piper betle, Picrorhiza kurroa, and so forth, and their active constituents reduced NSAIDs induced gastric ulcer via their antioxidative as well as immunomodulatory activity. Therefore, use of herbal formulations in daily life may prevent NSAIDs induced gastric ulceration and other side effects.